Ordered states in the Kitaev-Heisenberg model: From 1D chains to 2D honeycomb - Cliò Efthimia Agrapidis (Nature Portfolio, 2018)
Abstract We study the ground state of the 1D Kitaev-Heisenberg (KH) model using the density-matrix renormalization group and Lanczos exact diagonalization methods. We obtain a rich ground-state phase diagram as a function of the ratio between Heisenberg (J = cosϕ) and Kitaev (K = sinϕ) interactions. Depending on the ratio, the system exhibits four long-range ordered states: ferromagnetic-z, ferromagnetic-xy, staggered-xy, Néel-z, and two liquid states: Tomonaga-Luttinger liquid and spiral-xy. The two Kitaev points $${\boldsymbol{φ }}{\boldsymbol{=}}\frac{{\boldsymbol{π }}}{{\bf{2}}}$$ ϕ = π 2 and $${\boldsymbol{φ }}{\boldsymbol{=}}\frac{{\bf{3}}{\boldsymbol{π }}}{{\bf{2}}}$$ φ = 3 π 2 are singular. The ϕ-dependent phase diagram is similar to that for the 2D honeycomb-lattice KH model. Remarkably, all the ordered states of the honeycomb-lattice KH model can be interpreted in terms of the coupled KH chains. We also discuss the magnetic structure of the K-intercalated RuCl3, a potential Kitaev material, in the framework of the 1D KH model. Furthermore, we demonstrate that the low-lying excitations of the 1D KH Hamiltonian can be explained within the combination of the known six-vertex model and spin-wave theory.